2020
DOI: 10.1007/s00228-020-03016-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of tramadol and other analgesics following media attention and risk minimization actions from regulators: a Danish nationwide drug utilization study

Abstract: Purpose To describe the use of tramadol and other analgesics in Denmark focusing on the impact of media attention (June and December 2017) and regulatory actions (September 2017 and January 2018) on the use of tramadol. Methods Using nationwide registries, we identified all adults who filled a prescription for tramadol and other analgesics from 2014 to 2019. We described incidence rates, prevalence proportions, and total use of tramadol and other analgesics over time. We also described switching between anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…The use of tramadol has increased worldwide over the last decades. For example, in Denmark, its use doubled from 2011 to 2013 (Muller et al 2019 ), although a decline in prescription tramadol use was observed from 2014 to 2019 (Sorensen et al 2021 ). Mordecai et al ( 2018 ) mention several reasons for the increase in tramadol prescription and its consequences on public health in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…The use of tramadol has increased worldwide over the last decades. For example, in Denmark, its use doubled from 2011 to 2013 (Muller et al 2019 ), although a decline in prescription tramadol use was observed from 2014 to 2019 (Sorensen et al 2021 ). Mordecai et al ( 2018 ) mention several reasons for the increase in tramadol prescription and its consequences on public health in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…The use of tramadol has increased worldwide during the last decades. For example, in Denmark, it increased twice its use from 2011 to 2013, (Muller et al 2019), although a decline in tramadol use was observed from 2014 to 2019 (Sorensen et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that this preference for weak opioids has been influenced by requirements for additional documentation when prescribing strong opioids, which are classified as narcotics. Products containing tramadol were, however, rescheduled as narcotic in Sweden in 2012 [ 23 ] and in Denmark in 2017 [ 24 ], leading to a rapid reduction in tramadol utilisation in both countries [ 24 ]. In Iceland, the high prevalence and low intensity of opioid utilisation indicates that small amounts of especially codeine are being dispensed to a relatively high proportion of the older population.…”
Section: Discussionmentioning
confidence: 99%
“…As for opioids, the Nordic market has previously been dominated by the use of codeine and tramadol, commonly described as weak opioids, that have required less stringent documentation compared to strong opioids [ 22 ]. However, to reduce the use of tramadol, it has recently been scheduled as a narcotic in both Sweden and Denmark [ 23 , 24 ]. Opioid utilisation has been described for the overall population in some Nordic countries, but recent descriptions lack a full picture of the utilisation in the five countries [ 22 , 25 27 ].…”
Section: Introductionmentioning
confidence: 99%